Molecular identification of the genus Molicola larvae from swordfish (Xiphias gladius) captured in Sri Lanka by ribosomal subunit gene sequencing - DPN De Silva; JLCS Perera; HSD Fernando; RRMKP Ranatunga; BGDNK De Silva (Department of Aquaculture, 2021)
Swordfish (Xiphias gladius) is a migratory fish commercially exploited due to high export value. Presence of parasites in fish lead to economic losses in the export market and public health issues. This study was conducted to identify the parasite larvae inhabiting swordfish and to determine its phylogenetic origin using ribosomal subunit gene sequence. Parasite samples were extracted from swordfish muscles and five larvae belong to Molicola genus, confirmed by scolex morphology, were used for genomic DNA extraction. Polymerase chain reaction (PCR) was performed to amplify 18S and 28S ribosomal RNA (rRNA) subunit genes followed by Sanger sequencing. DNA sequences were edited by BioEdit software and assembled by CLC genomics version 8.0. Consensus sequences were aligned with NCBI blast to determine the species status. Isolated larval sequences were best aligned with genus Molicola followed by genus Gymnorhyncha. Out of the two published Molicola rRNA gene sequences, 99% identity was observed with Molicola sp. HP5 isolate from Indonesia. Due to lack of sequence data on other Molicola species (except M. thyristes) for comparison, our sequences were published as Molicola sp. Sri Lankan isolates. This is the first record of Molicola sp. in swordfish from Sri Lanka and the results will enhance the knowledge on the distribution of Molicola species while contributing to expand the genetic information on rRNA coding sequences.